Real‐life efficacy and safety of idelalisib in 55 double‐refractory follicular lymphoma patients. (24th August 2022) - Isidori, Alessandro; Loscocco, Federica; Visani, Giuseppe; Paolasini, Sara; Scalzulli, Potito; Musto, Pellegrino; Perrone, Tommasina; Guarini, Attilio; Pastore, Domenico; Mazza, Patrizio; Tonialini, Lorenzo; Pavone, Vincenzo; et al.
Summary: Idelalisib, a reversible inhibitor of PI3Kδ (phosphoinositide‐3 kinase delta), showed remarkable activity in the phase II DELTA trial, leading to its approval by the European Medicines Agency (EMA) in patients with relapsed/refractory (R/R) follicular lymphoma (FL). However, real‐life data on idelalisib are scarce. We treated 55 double‐refractory FL patients with idelalisib in a real‐life setting. With a median exposure to idelalisib of 10 months (range 1–43), overall response rate was 73%, the highest ever reported. Non‐haematological toxicities were mild and manageable. At 12 months, 80% of patients were alive, and 72% disease‐free. The efficacy and safety of idelalisib was confirmed in a real‐life setting.